The Impact of Drought Stress on Soil Microbial Community, Enzyme Activities and Plants - Bogati, Kalisa; Walczak, Maciej (Agronomy (Basel), 2022)
Nowadays, the most significant consequence of climate change is drought stress. Drought is one of the important, alarming, and hazardous abiotic stresses responsible for the alterations in soil environment affecting soil organisms, including microorganisms and plants. It alters the activity and functional composition of soil microorganisms that are responsible for crucial ecosystem functions and services. These stress conditions decrease microbial abundance, disturb microbial structure, decline microbial activity, including enzyme production (e.g., such as oxidoreductases, hydrolases, dehydrogenase, catalase, urease, phosphatases, β-glucosidase) and nutrient cycling, leading to a decrease in soil fertility followed by lower plant productivity and loss in economy. Interestingly, the negative effects of drought on soil can be minimized by adding organic substances such as compost, sewage slugs, or municipal solid waste that increases the activity of soil enzymes. Drought directly affects plant morphology, anatomy, physiology, and biochemistry. Its effect on plants can also be observed by changes at the transcriptomic and metabolomic levels. However, in plants, it can be mitigated by rhizosphere microbial communities, especially by plant growth-promoting bacteria (PGPB) and fungi (PGPF) that adapt their structural and functional compositions to water scarcity. This review was undertaken to discuss the impacts of drought stress on soil microbial community abundance, structure and activity, and plant growth and development, including the role of soil microorganisms in this process. Microbial activity in the soil environment was considered in terms of soil enzyme activities, pools, fluxes, and processes of terrestrial carbon (C) and nitrogen (N) cycles. A deep understanding of many aspects is necessary to explore the impacts of these extreme climate change events. We also focus on addressing the possible ways such as genome editing, molecular analysis (metagenomics, transcriptomics, and metabolomics) towards finding better solutions for mitigating drought effects and managing agricultural practices under harsh condition in a profitable manner.